2024
DOI: 10.3390/molecules29020435
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, and Antioxidant and Antimicrobial Activity of Oregano Essential Oil

Magdalena Walasek-Janusz,
Agnieszka Grzegorczyk,
Anna Malm
et al.

Abstract: Antimicrobial resistance (AMR) is a global public health problem, and the rapid rise in AMR is attributed to the inappropriate and/or overuse of antibiotics. Therefore, alternative antimicrobial agents, including those of natural origin, are being sought for the development of new drugs. The purpose of our study was to analyze the chemical composition, and antimicrobial and antioxidant activities of four oregano essential oils (OEOs) from Poland, Europe, Turkey and the USA. The antimicrobial activity (AMA) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Last but not least, our IBR analysis identified the ethanolic extracts of S. montana and O. vulgare as highly promising antibacterial agents. This observation is noteworthy as prior studies predominantly emphasized the antibacterial activity of their essential oils [ 50 , 61 , 84 ]. Our findings further reveal the promising antibacterial efficacy of their extracts, shedding light on their potential as a powerful natural defense against various aspects of bacterial infections.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Last but not least, our IBR analysis identified the ethanolic extracts of S. montana and O. vulgare as highly promising antibacterial agents. This observation is noteworthy as prior studies predominantly emphasized the antibacterial activity of their essential oils [ 50 , 61 , 84 ]. Our findings further reveal the promising antibacterial efficacy of their extracts, shedding light on their potential as a powerful natural defense against various aspects of bacterial infections.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies have explored the impact of extracts of Lamiaceae representatives on bacterial growth activity [ 40 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]; however, our literature review revealed that current research mainly focuses on the antibacterial properties of essential oils derived from Lamiaceae plants [ 12 , 50 , 60 , 61 , 62 ]. In our study, B. subtilis showed the highest susceptibility to the effects of Lamiaceae extracts, with H. officinalis and S. officinalis ethanolic and S. scardica methanolic extracts demonstrating the most potent growth-inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%